The Impact of Recent Chemotherapy Innovation on the Longevity of Myeloma Patients: U.S. and International Evidence - Frank Lichtenberg; Gisela Hostenkamp (Center for Economic Studies and ifo Institute (CESifo), 2013)
There were no innovations in chemotherapy for myeloma patients during the period 1977-1997, but there have been several important innovations since 1997. We investigate the impact of recent chemotherapy innovation on the longevity of myeloma patients using both time-series U.S. data and longitudinal data on 26 countries.In the US, the average annual rate of increase of life expectancy of myeloma patients at time of diagnosis was over five times as large during 1997-2005 as it had been during 1975-1997. We estimate that almost two-thirds (0.99 years) of the 1997-2005 increase in life expectancy was due to the increase in the number of chemotherapy regimens now preferred by specialists, and that the cost per U.S. life-year gained from post-1997 chemotherapy innovation did not exceed 45,551.We also investigate the impact of chemotherapy innovation on the myeloma mortality rate using longitudinal country-level data on 26 countries during the period 2005-2009. Countries that had larger increases in the number of chemotherapy regimens had larger subsequent declines in myeloma mortality rates, controlling for other factors. The estimates imply that chemotherapy innovation reduced the age-adjusted myeloma cancer mortality rate by about 3.1% during the period 2005-2009.
Keywords: I12; L65; O33; 330